If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X) + (x + -3) + (3x) + (3x + 4) = 89 X + (x + -3) + (3x) + (3x + 4) = 89 Reorder the terms: X + (-3 + x) + (3x) + (3x + 4) = 89 Remove parenthesis around (-3 + x) X + -3 + x + (3x) + (3x + 4) = 89 Reorder the terms: X + -3 + x + (3x) + (4 + 3x) = 89 Remove parenthesis around (4 + 3x) X + -3 + x + (3x) + 4 + 3x = 89 Reorder the terms: -3 + 4 + X + x + (3x) + 3x = 89 Combine like terms: -3 + 4 = 1 1 + X + x + (3x) + 3x = 89 Combine like terms: x + (3x) = 4x 1 + X + 4x + 3x = 89 Combine like terms: 4x + 3x = 7x 1 + X + 7x = 89 Solving 1 + X + 7x = 89 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + X + -1 + 7x = 89 + -1 Reorder the terms: 1 + -1 + X + 7x = 89 + -1 Combine like terms: 1 + -1 = 0 0 + X + 7x = 89 + -1 X + 7x = 89 + -1 Combine like terms: 89 + -1 = 88 X + 7x = 88 Add '-7x' to each side of the equation. X + 7x + -7x = 88 + -7x Combine like terms: 7x + -7x = 0 X + 0 = 88 + -7x X = 88 + -7x Simplifying X = 88 + -7x
| 3+x(3+x)=73 | | 0.1=250 | | 2800=x-(x*0.2) | | 2800=x-(x*0.25) | | 1500=x-(x*0.2) | | 2000=x-(x*0.2) | | 4500=x-(x*0.2) | | 2y+2x-5=1 | | 2x+2y-5=1 | | 2200=x-(x*0.2) | | 800=x-(x*0.2) | | 1=-(2)+3 | | x^2-(2k+3)x+3k=0 | | 6000=x-(x*0.25) | | 6000=x-(x*0.3) | | 2=-(1)+3 | | 20+4K=-7K-1 | | 103.588=10x+2y | | 2=-(1+3) | | 3500=x-(x*0.2) | | 2+3(1)=5 | | 6x+3y=5y | | -sinx*tanx= | | 14-3d=-5d+12 | | tanx= | | 5x^3y-5xy^3+6x^2y-6xy^2= | | 7c+9-7c+6= | | x^2+100x=2400 | | 3z+5=-13 | | 2(2y+7)+3(3y-5)=3(4y+5)-1 | | 4(x-3)=-2x-4 | | 5-4x=25+6x |